PENGELOLAAN PASAR KAGET OLEH DINAS PASAR KOTA PEKANBARU DI KECAMATAN SAIL - Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
In Pekanbaru city, especially in Sail District, the number of seasonal market has increased significantly. It has given both positive and negative effects to the society. The positive effect is that it makes people easily get access to go shopping and fulfill their daily needs. Moreover, the price of goods in the seasonal market is cheaper than that in the usual traditional market. On the other hand, the negative effect which occurs is that the arbitrary opening of the seasonal market has reduced the function of the traditional market. Furthermore, it usually causes traffic jam because the seasonal market is opened in the wide field and the vendors sell their goods near the roadside. As a result, it disturbs the traffic stream and makes the road users uncomfortable.According to the Market Office of Pekanbaru, the seasonal market is included as a traditional market. Therefore, it is also ruled by Pekanbaru regional regulation number 9/2014 about the management of traditional market, shopping center, and supermarket. In doing research about the management of seasonal market by Market Office of Pekanbaru in Sail District, the researcher used Gorge R. Terry’s theory about management. He states that there are four components of management; they are planning, organizing, actuating, and controlling. The technique that is used in this research is descriptive qualitative technique which uses observation to explain and prove the data of the research.The management of the seasonal market’s development nowadays is relatively disappointing. The management only includes collecting the data related to the existence of seasonal market. Indeed, the action to relocate the vendors from the seasonal market to provided public traditional market has not been done.Keywords : Management, Seasonal market